Augmented reality as a pathway to inclusive learning: Empowering students with intellectual disabilities to build literacy and numeracy skills - Chandra, Detri Amelia; Muslim; Dwiana, Ari Aprilia; Muhajirin, Ahmad; Silitonga, Wulan Afrilia (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Purpose: The study aims to design, validate, and evaluate the effectiveness of Augmented Reality (AR)-based learning media to enhance literacy and numeracy among students with intellectual disabilities at Rokan Hulu Special Needs School. Method: This research applied the Multimedia Development Life Cycle (MDLC) model, following six stages: concept, design, material collection, assembly, testing, and distribution. The media were validated by content and media experts, and its effectiveness was assessed using a pretest-posttest design involving six students. Statistical analyses, including paired-sample t-tests and N-Gain calculations, were used to measure the improvement in students' skills. Findings: The AR-based media was highly feasible, with expert validation scores confirming its content relevance and technical quality. Statistical analyses revealed significant improvements in both literacy and numeracy skills, with large effect sizes, suggesting that AR-based learning effectively supports skill development in students with intellectual disabilities. Significance: The study shows that AR technology offers a promising tool for improving literacy and numeracy among students with intellectual disabilities. The findings highlight the potential of AR to enhance engagement, motivation, and learning outcomes in inclusive educational settings.